traY and traI are required for oriT-dependent enhanced recombination between lac-containing plasmids and lambda plac5. - Carter, J R (1991)
Recombination between F42lac and lambda plac5 is typically 20- to 50-fold more efficient than recombination between chromosomal lac and lambda plac5. This enhancement of recombination requires trans-acting factors located in the promoter-distal and promoter-proximal regions of the main traY-to-traI (traZ) operon. By testing the ability of deletion mutants of tra to support enhanced recombination, we have identified traY as the only product has been ruled out. We also report that traI is the only gene from the promoter-distal end of the traY to traI operon that is required for recombination enhancement. Of the two proposed domains of traI, we conclude that the oriT-nicking activity is essential, whereas the helicase activity is largely dispensable. The possibility of a third traI activity is also discussed.